AI-Based Market Intelligence as a Strategic Tool for Local MSME Development in West Java - Suhendri; Dina Hidayat; Novasa Adiyani; Endang Ahmad; Fanissa Narita; Nico Irawan; Egi Sucianti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Local Micro, Small, and Medium Enterprises (MSMEs) in Purwakarta, particularly ceramic craftsmen in Plered District, have strong potential to contribute to regional economic growth and enter broader export markets. However, they still face several major problems, including inconsistent product quality, limited design innovation, weak packaging standards, insufficient branding, limited digital marketing capacity, and low readiness to meet export market requirements. The gap identified in this activity is the limited integration between traditional ceramic production practices and modern market-oriented strategies, especially in quality control, product differentiation, digital promotion, and export preparation. Current developments show that MSME competitiveness is increasingly influenced by product innovation, digital marketing, branding, packaging quality, and export readiness. Therefore, this community service activity applied a participatory mentoring approach through field observation, discussion, consultation, and practical recommendations for ceramic craftsmen in Plered. The proposed solution focused on strengthening product quality, improving design and packaging, developing brand identity, optimizing digital marketing, and preparing MSMEs for export-oriented market access. The results indicate that the mentoring activity increased the awareness of ceramic craftsmen regarding product competitiveness, market standards, and the importance of continuous innovation. In conclusion, ceramic MSMEs in Plered have strong potential to improve their competitiveness in the export market when supported by consistent mentoring, quality standardization, strategic branding, digital promotion, and collaboration between higher education institutions, local industry, and community stakeholders.